Simplified traction prediction for highly loaded rolling/sliding EHL contacts. (August 2020) - Liu, H.C.; Zhang, B.B.; Bader, N.; Venner, C.H.; Poll, G.
Abstract: A simplified traction prediction approach has been developed for highly loaded EHL contacts accounting for non-Newtonian and thermal effects. For validation, a reference fluid squalane was used for traction measurements at high Hertzian contact pressures ( 1.25 to 2.66 GPa ) at three velocities of 5, 10 and 15 m / s . Good agreement was seen for traction curves in a semi-log scale at a low speed of 5 m / s, whereas for higher speeds at 10 m / s and 15 m / s, the measured traction curves are lower than the predicted ones. This reduced friction in the experimental results is caused by the increase in mass temperature of the discs. Two possible mechanisms for this reduced friction due to solid body temperature effects are discussed. Highlights: This simplified method predicts traction without solving Reynolds and elastic deformation equations. Non-Newtonian and thermal effects are modelled. A model fluid, squalene, was used for both simulations and traction experiments. Traction curves were compared with semi-log plots over a wide range of operating conditions. Solid body temperature effect reduces the measured traction at high-speed conditions.